Elision in Students' Pronunciation during Presentation - Septiana Iman Nasrulloh; Salman Yasri; Evie Kareviati (IKIP Siliwangi, 2019)
Discourse analysis is a broad term for the study of the ways in which language is used in texts and contexts. Elision is very simply the omission of certain sound of the words in certain contexts. In this study, the writers use qualitative method of discourse analysis to examine and find out the types of elision that used by students in presentation. The data were taken from the recordings of two group students’ presentations on the class A2 English Education 2015 on IKIP Siliwangi Bandung with the subject “Theories of Interpreting”. The result shows that there are three types of elision used by the students. They are apheresis elision, syncope elision, and apocope elision the students use 6 words of apheresis elision, 22 words of syncope elision, 25 words of apocope elision during the presentation of two group students. It can be concluded that the commonly used is apocope ellision as many as 25 word.